Novel Chalcone BDD-39 Mitigated Diabetic Nephropathy through the Activation of Nrf2/ARE Signaling - Adelusi, Temitope; Li, Xizhi; Xu, Liu; Du, Lei; Hao, Meng; Zhou, Xueyan; Chowdhry, Apu; Sun, Ying; Gu, Xiaoke; Lu, Qian; Yin, Xiaoxing (Current Molecular Pharmacology, 2022)
Background: In this study, we investigated the Nrf2/ARE signaling pathway activating capacity of Biphenyl Diester Derivative-39 (BDD-39) in diabetic nephropathy in order to elucidate the mechanism surrounding its antidiabetic potential. Objectives: Protein expressions of Nrf2, HO-1, NQO-1 and biomarkers of kidney fibrosis were executed after which mRNA levels of Nrf2, HO-1 and NQO-1 were estimated after creating the models following BBD-39 treatment. Methods: Type 2 diabetes model was established in mice with high-fat diet feeding combined with streptozocin intraperitoneal administration. The diabetic mice were then treated with BDD-39 (15, 45mg· kg-1· d-1, ig) or a positive control drug resveratrol (45mg· kg-1·d-1, ig) for 8 weeks. Staining techniques were used to investigate collagen deposition in the glomerulus of the renal cortex and also to investigate the expression and localization of Nrf2 and extracellular matrix (ECM) proteins (collagen IV and laminin) in vitro and in vivo. Furthermore, we studied the mechanism of action of BDD-39 using RNA-mediated Nrf2 silencing technique in mouse SV40 glomerular mesangial cells (SV40 GM cells). Results: We found that BDD-39 activates Nrf2/ARE signaling pathway, promotes Nrf2 nuclear translocation (Nrf2nuc/Nrf2cyt) and modulate prominent biomarkers of kidney fibrosis at the protein level. However, BDD-39 could not activate Nrf2/ARE signaling in RNA-mediated Nrf2-silenced HG-cultured SV40 GM cells. Conclusion: Taken together, this study demonstrates for the first time that BDD-39 ameliorates experimental DN through attenuation of renal fibrosis progression and modulation of Nrf2/ARE signaling pathway.
Keywords: Nrf2/ARE signaling pathway